PEMBERIAN SARI KURMA TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL - Eni, Eka Fitri; Imanah , Norif Didik Nur; Sukmawati , Ellyzabeth; Aksari , Septi Tri (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Anemia is one of the problems that occurs during pregnancy which can be caused by a lack of iron which is needed for the formation of hemoglobin. Anemia is characterized by the characteristics of feeling easily tired, weak, pale, dizzy and heart palpitations. Treatment of anemia in pregnant women can be done with non-pharmacological measures, namely by administering date palm juice. This research aims to determine the effectiveness of giving date palm juice to increase hemoglobin in pregnant women using qualitative research with a case study approach and data sources and types of data using interviews, examination and observation. The implementation technique was carried out by Mrs. S by giving 10ml of date juice consumed 3 times a day before eating or the equivalent of 1 tablespoon and carrying out an evaluation after 7 days of giving date palm juice and the results showed that there was an increase in hemoglobin levels after being given date palm juice, marked by an increase in hemoglobin levels to 10. 7 gr/dl, so that giving date palm juice has an impact on increasing hemoglobin levels.